Assessment of Heavy Metal Contents in Raw Cow Milk Samples from Selected Local Government Areas in Kano State, Nigeria - Tobi, Rasheed Jamiu; Salami, John Tolulope; Audu, Abdulrahman A. (Asian Journal of Science and Applied Technology, 2023)
The study assessed the concentration of copper (Cu), Lead (Pb), Zinc (Zn) and Iron (Fe) in cow milk samples (raw) got from selected Local Government Areas, Kano State namely; (Gwale (Sample Location A), Dala (Sample Location B) and Ungogo (Sample location C) within Kano state, Nigeria. Heavy metal determination was done according to standard produres. Heavy metal concentrations (Cu, Fe, Zn, and Pb) were assessed by the use of Atomic Absorption Spectrometer (AAS). The content of Copper (Cu) in the sample of cow milk from the three Local Government (Gwale, Dala and Ungogo) were 0.0584 mgl-1, 0.0714 mgl-1 and 0.2604 mgl-1 respectively. The concentration of Zinc (Zn) in the raw cow milk samples from the three Local Government (Gwale, Dala and Ungogo) were 0.1336 mgl-1, 0.1148 mgl-1 and 0.1595 mgl-1 respectively. The levels of Iron (Fe) from the samples of cow milk (raw) from the selected Local Government areas (Gwale, Dala and Ungogo) were 0.7319 mgl-1, 0.6438 mgl-1 and 0.8709 mgl-1 respectively. The levels of Lead (Pb) from the selected Local Government areas (Gwale, Dala and Ungogo were 0.0350 mgl-1, 0.0390 mgl-1 and 0.4100 mgl-1 respectively. The result shows that the Fe and Pb concentrations in raw cow milk samples collected from all the three Local Government areas (Gwale, Dala and Ungogo) were all above the WHO permissible limits. However, the concentrations of Zn and Cu in the cow milk samples (raw) obtained from the area remained within the World Health Organization (WHO) permissible limit. Routine and further study is required to determine the heavy metals status in cow milk from other LGAs of the State to ascertain the safe levels of cow milk products to consumers in the area.